Membros: v. 11, n. 1 (2013) - ., .. (RENOTE, 2013)
Alexandra Lorandi Macedo - UFRGS Alessandra Pereira Rodrigues - Instituto Federal Sul Riograndense - Pelotas Alexandre Ribeiro - UCS Ana Carolina B de Marchi - UPF Ana Marli Bulegon - UNIFRA Barbara Gorziza Avila - UFRGS Carla Beatris Valentini - Universidade de Caxias do Sul Carlos Tadeu Queiroz de Morais - PGIE - UFRGS Dinorá Morais de Fraga - PPGIE Elisa Boff - UCS Eliseo Reategui - FACED/PGIE - UFRGS Érico H. Amaral - UNIPAMPA Evandro Alves - CINTED/UFRGS Gilse Antoninha Morgental Falkembach - UFSM/CINTED Janete Sander Costa - ULBRA Joice Otsuka - UFSCAR José Valdeni Lima - PGIE/UFRGS Louise Jeanty de Seixas - Faculdade de Farmácia/UFRGS Magda Bercht - Instituto de Informática/PGIE - UFRGS Marcelo Augusto Rauh Schmitt - Instituto Federal do Rio Grande do Sul Marcelo Foohs - Faculdade de Educação / UFRGS Marcia Cristina Moraes - PUCRS Marcia Rodrigues Notare - UNISINOS Marcus Vinícius de Azevedo Basso - Instituto de Matemática/UFRGS Maria Rosangela Bez - UFRGS Marina Nakayama - UFSC Marlise Geller - ULBRA Marta Rosecler Bez - Fevale Michelle Denise Leonhardt - Departamento de Informática Aplicada/UFRGS Patrícia Alejandra Behar - FACED/PGIE - UFRGS Querte Mehlecke - FACCAT/RS Renato Dutra - Universidade Anhembi Morumbi Ricardo Azambuja Silveira - INF/UFSC Roberto dos Santos Rabello - Universidade de Passo Fundo Roseclea Medina - UFSM Silvia Meirelles Leite - UFPEL Valéria Costa - PPGIE Coordenação : Liane Margarida Rockenbach Tarouco - CINTED/UFRGS Eliseo Reategui - PGIE/UFRGS